Golf - Edited by Cadogan, James (London Star Fire Books, 2008)
Part of a series of gift books featuring pictures and text celebrating a particular sport throughout the years, this work presents a host of fascinating facts and figures about your favorite golfing sportsmen, tournaments and kit alongside pictures.
Include Color Illustrations.
Sporting Memoirs.
Keywords: Golf -- Golf -- Miscellanea